Fire buckling curves for torsionally sensitive steel members subjected to axial compression. (27th October 2021) - Possidente, Luca; Tondini, Nicola; Battini, Jean-Marc
Abstract : Purpose: Buckling should be carefully considered in steel assemblies with members subjected to compressive stresses, such as bracing systems and truss structures, in which angles and built-up steel sections are widely employed. These type of steel members are affected by torsional and flexural-torsional buckling, but the European (EN 1993-1-2) and the American (AISC 360-16) design norms do not explicitly treat these phenomena in fire situation. In this work, improved buckling curves based on the EN 1993-1-2 were extended by exploiting a previous work of the authors. Moreover, new buckling curves of AISC 360-16 were proposed. Design/methodology/approach: The buckling curves provided in the norms and the proposed ones were compared with the results of numerical investigation. Compressed angles, tee and cruciform steel members at elevated temperature were studied. More than 41, 000 GMNIA analyses were performed on profiles with different lengths with sections of class 1 to 3, and they were subjected to five uniform temperature distributions (400–800 C) and with three steel grades (S235, S275, S355). Findings: It was observed that the actual buckling curves provide unconservative or overconservative predictions for various range of slenderness of practical interest. The proposed curves allow for safer and more accurate predictions, as confirmed by statistical investigation. Originality/value: This paper provides new design buckling curves for torsional and flexural-torsional buckling at elevated temperature since there is a lack of studies in the field and the design standards do not appropriately consider these phenomena.